Development of a Digital Electronics Trainer Kit as a Learning Medium for Basic Concepts of Electricity and Electronics in Vocational High Schools - Fadel, Fadel Montoya; Irwanto, Irwanto; Bagus Dwi Cahyono (The Future of Education Journal, 2025)
The learning process is the main foundation in shaping students' competencies, especially in Vocational High Schools (SMK) which emphasize the balance between theory and practice. This research aims to develop learning media in the form of a digital electronics trainer kit to improve understanding of basic concepts of electricity and electronics, especially for class X students majoring in Industrial Electronics at SMKN 8 Tangerang City. This research uses the Research and Development (R&D) method with the Four-D development model which includes the define, design, develop, and disseminate stages. Data were collected through interviews, questionnaires, and media and material expert validation using Aiken's V formula to measure the content validity of the instrument. The validation results showed an average Aiken's V value of 0.948 for media and 0.944 for materials, both in the “very valid” category. The media feasibility test by experts obtained an average score of 138.3, while the feasibility of the material by experts gave an average score of 99.6. Student respondents gave an average score of 68.5 out of a total score of 2057, indicating the media was in the “very feasible” category. These findings indicate that the trainer kit developed is effective in increasing learner engagement and understanding in a practical and contextual manner. The implication of this research shows the importance of integrating practice-based learning media in SMK. It is recommended that similar developments be widely disseminated through collaboration between schools to strengthen the quality of vocational learning in Indonesia.